Taste of modernity : Sufism, Salafiyya, and Arabism in late Ottoman Damascus - Weismann, Itzchak (Islamic history and civilization ;, 2001)
Modernization in the Muslim world was determined by the two interrelated processes of indigenous state formation and European economic penetration. This study traces the emergence of modern Islam and examines the relationship of Islamic modernization to the rise of Arab Nationalism.